2000
DOI: 10.1210/endo.141.3.7399
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor Expression and Regulation within the Testis

Abstract: Leukemia inhibitory factor (LIF) is a pleiotropic cytokine known to control the proliferation and survival of stem cells including primordial germ cells and gonocytes. This led us to study the origin and regulation of testicular LIF. The LIF transcript was detected in the rat testis by RT-PCR from 13.5 days postcoitum until adulthood. LIF expression was investigated further in vitro in seven different highly purified testicular cell populations using RT-PCR and bioassays combined with neutralization experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…One possible explanation is that these cells are initially more diffusely distributed but then form aggregates under the influence of local growth factors. One such growth factor that may be active in this respect is LIF, which is primarily produced by peritubular myoid cells (28). We herein showed that LIF caused dose-dependent increases in the cluster size of FLCs in vitro.…”
Section: Resultsmentioning
confidence: 57%
“…One possible explanation is that these cells are initially more diffusely distributed but then form aggregates under the influence of local growth factors. One such growth factor that may be active in this respect is LIF, which is primarily produced by peritubular myoid cells (28). We herein showed that LIF caused dose-dependent increases in the cluster size of FLCs in vitro.…”
Section: Resultsmentioning
confidence: 57%
“…LIF is required for long-term self renewal of neural stem cell cultures (21) and for maintenance of primordial germ cells in vitro (22). In the rat testis, LIF is detectable from 13.5 days of gestation onward and is predominantly expressed by peritubular myoid cells surrounding the seminiferous tubules (23). In the first week postnatally, the peritubular cells have a fibroblastic ultrastructure, appearing spindle-shaped by light microscopy (2), and form a two-to three-cell-layer-thick boundary tissue (lamina propria).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of LIF, the factor has been shown to display a numerous pluripotent actions on various types of cells and tissues including macrophage cell line (Gearing et al, 1987), embryonic stem cells (Smith and Hooper, 1987;Williams et al, 1988;Duval et al, 2000), primordial germ cells (Hara et al, 1998), uterus (Yue et al, 2000), testis (Piquet-Pellorce et al, 2000), neuronal cell (Turnley and Bartlett, 2000), heart (Wang et al, 2001), skeletal muscle cell (White et al, 2001), mast cell (Hiragun et al, 2000;Tanaka et al, 2001), bone cell (Dazai et al, 2000), hypothalamus (Chesnokova and Melmed, 2000), anterior pituitary cell (Schwartz et al, 1999), adrenal gland (Bamberger et al, 2000), adipocyte (Aubert et al, 1999), and skin . Thus, LIF is a pleiotropic cytokine able to act in a variety of cells and tissues in both adult and embryo.…”
Section: Discussionmentioning
confidence: 99%